ANALYSIS OF THE CAUSES OF BULLYING AMONG STUDENTS IN MI – ISLAMIYAH PLOSOBUDEN - Muslimatin, Siti Rahayu Nasichatu; Nichlah, Ayun (EDU-KATA, 2024)
Researchers conducted research at Mi - Islamiyah Plosobuden regarding the increasing number of bullying cases, the research was qualitative in nature and carried out direct observations in the field regarding bullying cases. Researchers collected data using test and interview methods. Data collection uses in-depth interviews. Data were analyzed by triangulation. Data collection techniques were carried out using triangulation or combination methods. Data was collected by observation, interviews, documentation. data analysis through data reduction, data presentation, drawing conclusions or verification. where the aim is to find out systematically about the focus of research which discusses the prevalence of bullying cases. It can be concluded that bullying cases at Mi-Islamiyah Plosobuden are still quite minimal due to good communication between teachers, students and parents. And there is an appeal from the school for students and girls not to bully. In this article, researchers will discuss several factors and the meaning of bullying.